Innovative Tele-Instruction Approach Impacts Basic Life Support Performance: A Non-inferiority Trial - Schauwinhold, Michael Tobias; Schmidt, Michelle; Rudolph, Jenny W.; Klasen, Martin; Lambert, Sophie Isabelle; Krusch, Alexander; Vogt, Lina; Sopka, Saša (Frontiers in Medicine, 2022)
Background: Sustaining Basic Life Support (BLS) training during the COVID-19 pandemic bears substantial challenges. The limited availability of highly qualified instructors and tight economic conditions complicates the delivery of these life-saving trainings. . Consequently, innovative and resource-efficient approaches are needed to minimize or eliminate contagion while maintaining high training standards and managing learner anxiety related to infection risk. Methods: In a non-inferiority trial 346 first-year medical, dentistry, and physiotherapy students underwent BLS training at AIXTRA – Competence Center for Training and Patient Safety at the University Hospital RWTH Aachen. Our objectives were 1) to examine whether peer feedback BLS training supported by tele-instructors matches the learning performance of standard instructor-guided BLS training for laypersons; and 2) to minimize infection risk during BLS training. Therefore, in a parallel group design, we compared arm 1) Standard Instructor Feedback (SIF) BLS training (Historical control group of 2019) with arm 2) a Tele-Instructor Supported Peer-Feedback (TPF) BLS training (Intervention group of 2020). Both study arms were based on Peyton’s 4-step approach. Before and after each training session, objective data for BLS performance (compression depth and rate) were recorded using a resuscitation manikin. We also assessed overall BLS performance via standardized instructor evaluation and student self-reports of confidence via questionnaire. Non-inferiority margins for the outcome parameters and sample size calculation were based on previous studies with SIF. Two-sided 95% confidence intervals were employed to determine significance of non-inferiority. Results: The results confirmed non-inferiority of TPF to SIF for all tested outcome parameters. A follow-up after two weeks found no confirmed COVID-19 infections among the participants. Conclusion: Tele-instructor supported peer feedback is a powerful alternative to in-person instructor feedback on BLS skills during a pandemic, where infection risk needs to be minimized while maximizing the quality of BLS skill learning.